PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIA SMPIT AZ-ZUHRA PEKANBARU - Nuriatama '; Susda Heleni; Kartini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve the learning process and improve learning achievement by applying the mathematical inquiry learning model on students of class VIIA SMPIT Az-Zuhra Pekanbaru. The subjects were 20 students of class VIIA SMPIT Az-Zuhra Pekanbaru Academic Year 2015/2016, with heterogeneous acaemic ability levels. This study consists of two cycles, in which each consists of four phases: planning, implementation, observation and reflection. At the end of each cycle, a daily test is given to the students. Data of the research are collected trough observation and the daily tests. An action is categorized to be successful if there is improvement in learning and the number of students who achieve the minimum completeness criteria (KKM) increases in the daily est I and test II. The research findings reveal that the activities of teachers and students run well as they were planned. Most students participate in the learning process actively, such as by discusing in determining hypotheses and collecting data, presenting the Student Worksheet (LKS), responding to their classmates’ presentation and concluding lessons. Therefore, it can be said that there is improvement in the learning process of each meeting. Besides the number of students who achieves KKM on a base score is 65% on daily test I (first cycle) and 75% on daily test II (second cycle) is 80%. The percentage achievement of KKM also shows an increase from before to after the action taken so that it can be concluded that the learning achievement of te student s also increases. The result of this study show that learning by the inquiry model can improve the learning process and improve mathematics learning achievement of students of class VIIA SMPIT Az-Zuhra Pekanbaru of the second semester of 2015/2016,Key Words: Mathematical Learning Achievement, The Inquiry Learning Model, Class Room Action Research